Developed of a cartesian CNC system for plasma metal sheet cutting (2019)
A Cartesian system was one of the first mechanism used to carried out a kinematical model, which characterise its advantages and restrictions in order to enhance different motions for industrial applications. This paper describes one of the most used applications in the industry called Computerized Numerical Control (CNC) used as a machine automated tool. The project development is divided into two large structures, the mechanical system and the electronic system. The 3 DOF automated CNC machine is driven with transmission by tooth-belt and spindle attached with to one manual plasma cutting equipment; with the constraint of generation of high index of electromagnetic interference due to its configuration of arc start by high frequency. It limitations was solved and highly decrease thanks to the implementation of complementary electronic designs such as filters, opto-couplers and a physical grounded. The execution of G-codes is compliances with established technical standards ensuring a uniform fluid-arc and safe behaviour.